La Tinta Bay Chacachacare, Trinidad - (:unkn) unknown (Bonanza Smith Bros. and Co.,[Trinidad and Tobago], 2011)
The postcard shows La Tinta Bay, a popular beach on the island of Chacachacare, the westernmost of the Bocas Islands which belong to Trinidad and Tobago. Affixed to the postcard is a penny postage stamp.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; [1907]; Beaches--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Bays--Trinidad and Tobago; Islands--Trinidad and Tobago; Chacachacare